(untitled) (Applied Biological Research, 2014)
An efficient protocol for propagation of Rauvolfia serpentina through in vitro culture was standardized. Of the various combinations of phyto hormones evaluated, 0.5 mg L-1indole acetic acid (IAA) +0.5 mg L-1 benzyl amino purine (BAP) + 1.0 mg L-1kinetin highly favoured callus induction (32.8%). High callus-mediated shoot regeneration was seen on MS medium supplemented with 1.0 mg L-1IAA + 0.5 mgL-1BAP + 0.5 mg L-1kinetin. Low auxin (IAA, 0.5 mg L-1) with higher concentration of cytokinin (0.5 mgL-1BAP +1.0mg L-1kinetin) gave higher shoots culture-1 (6.6) with mean shoot length of 3.2 cm. In direct shoot regeneration, best growth of axillary shoots was achieved in MS medium supplemented with0.2 mg L-1IAA + 0.2 mg L-1 BAP + 0.2 mg L-1kinetin with maximum shoots culture-1(10.0) and shoot length (4.4 cm). The root induction was highest (84.3%) in MS medium supplemented with IBA (0.5 mg L-1). The rooted plantlets were successfully established in field.